First case report of bacteremia caused by Solobacterium moorei in China, and literature review - Liu, Wen-Jing; Xiao, Meng; Yi, Jie; Li, Ying; Kudinha, Timothy; Xu, Ying-Chun (BMC infectious diseases, 2019)
Solobacterium moorei, the only species in the genus Solobacterium, is a Gram-positive, non-spore-forming, strict anaerobic, short to long bacillus. It has rarely been documented to cause blood stream infections. Here we report the first case of bacteremia caused by S.moorei in China. A 61-year-old male presented to Peking Union Medical College Hospital (Beijing) with thrombotic thrombocytopenic purpura (TTP) and several other underlying diseases. He also had persistent coma accompanied by intermittent convulsions, halitosis, and intermittent fever. Blood cultures taken when the patient had a high fever were positive, with the anaerobic bottle yielding an organism identified as S.moorei by 16S rRNA gene sequencing, whilst the aerobic bottle grew Streptococcus mitis. After replacement of venous pipeline, and empirical use of vancomycin and meropenem, the patient's body temperature and white blood cell count returned to normal. Unfortunately, the patient died of severe TTP. This is the first case report of S. moorei isolation from blood stream in China. 16S rRNA gene sequencing is the only method that can identify S. moorei. Blood cultures must be taken before administration of antibiotics, and anaerobic culture should be considered for such rare pathogens in patients with oral diseases and immune deficiency.